Drawn into Dancing and Danced into Drawing: Exploring Deleuze’s Lines of Flight through Dancing–Drawing Approaches in Early Childhood Dance Pedagogies - Colliander, Tuire (Senter for dansepraksis; Sciendo, 2024)
This article explores Deleuze and Guattari’s (1987) notion of ‘lines of flight’ as a philosophical concept and a phenomenon in dance pedagogical learning events by focusing on approaches combining dancing and drawing in an early childhood educational context. I share how the enquiry has been guided not only through the concept of thinking with theory (Jackson and Mazzei 2023) but also through dancing with theory through a series of creative approaches. This study is situated in the field of artistic research, with its theoretical framework in post-human theories (Barad 2007), intra-active pedagogy (Lenz Taguchi 2010) and assemblage (Deleuze and Guattari 1987) thinking. Diffractive reading (Barad 2007) is used in narrating the key moments, theorised as translations, that have been significant in researching the lines of flight and the intra-active relationship between drawing and dancing. The central claim is that working with dancing– drawing assemblages may expand children’s potential entry points and modes of participation. This can support more diverse, inclusive and participatory forms of dance pedagogies. Through dancing–drawing approaches, dance improvisation may become a mode of multimodal meaning-making, fostering rich and varied artistic experiences for children where embodied and artistic thinking intersect in novel ways.
Keywords: tanssi; pedagogiikka; varhaiskasvatus; taiteellinen tutkimus; filosofia